Recent Changes in Patterns of Mammal Infection with Highly Pathogenic Avian Influenza A(H5N1) Virus Worldwide - Plaza, Pablo I. (2024)
We reviewed information about mammals naturally in- fected by highly pathogenic avian influenza A virus subtype H5N1 during 2 periods: the current p2019). In the current panzootic, 26 countries have reported >48 mammal species infected by H5N1 virus; in some cases, the virus has affected thousands of in- dividual animals. The geographic area and the number of species affected by the current event are considerably larger than in previous waves of infection. The most plausible source of mammal infection in both periods appears to be close contact with infected birds, including their ingestion. Some studies, especially in the current panzootic, suggest that mammal-to-mammal transmission might be responsible for some infections; some mu- tations found could help this avian pathogen replicate in mammals. H5N1 virus may be changing and adapting to infect mammals. Continuous surveillance is essential to mitigate the risk for a global pandemic.